Importance of FDI on the Growth of Pakistan and Armenia - Najaf, Rabia; Najaf, khakan (Social Science Learning Education Journal, 2016)
The main objective of this paper is to find out the impact of impact of foreign direct investment on the economic growth of Pakistan and Armenia. For this purpose, we have used the secondary data .our study is showing that the foreign direct investment level is increasing in some countries and decreasing in some countries due to terrorism. In 1992, the level of foreign direct investment in Pakistan were 258.44 US at the same time there were foreign direct investment were low in Armenia. In the year of 2007, the level of foreign direct investment were 4374 US and at the same year the inflows of foreign direct investment in Armenia were 299US.Our paper is trying to show that education, power sector and telecom are known as the most profitable sector .the basic aim of this paper is that to show that foreign direct investment has the crucial role for the development of welfare of society.